Miscarriage perceptions and experiences among Saudi women - A. A. Rouzi; R. Alamoudi; J. Turkistani; N. Almansouri; S. Alkafy; N. Alsinani; A. Wazzan (Clinical and Experimental Obstetrics & Gynecology)
Objectives: To assess miscarriage perceptions and experiences of Saudi women. Materials and Methods: Between June 1, 2015, and August 30, 2016, women attending the obstetrics and gynaecology clinics at King Abdulaziz University Hospital in Jeddah (KAUH), Saudi Arabia were asked to participate in a cross-sectional survey. Demographic information, miscarriage opinions, and perceived causes were acquired from the entire cohort. Miscarriage data were obtained from women with miscarriage experience. Results: In a convenience sample of 296 women aged 18 to 57 years, 247 (83.4%) had never become pregnant, of whom 81 (32.8%) had a miscarriage history. Guilt, shame, and feeling alone were reported by 35%, 14%, and 22% of women after a miscarriage, respectively, and 10% reported all three, and 47% reporting none of these feelings. Only 14 (17%) were given a medical cause for the miscarriage, of whom five (36%) believed they had done something to cause it or could have done something to prevent it, compared with 35 of 67 (52%) women who were not given a reason for their miscarriage (p = 0.260). In the entire cohort, the most commonly agreed to causes of miscarriage were stressful event (72%), destiny/fate (65%), long-term stress (64%), lifting (57%), and past abortion (57%). Conclusions: While most participants with miscarriages reported receiving adequate support, there was inadequate knowledge about the causes of miscarriage. New education and support policies are warranted, particularly with regards to behaviours that do not need to be avoided for fear of miscarriage.